Misperceived social norms and political accountability: Evidence and theory - Shuhei Kitamura; Ryo Takahashi; Katsunori Yamada (Osaka University, Institute of Social and Economic Research (ISER), 2025)
Electoral accountability is a cornerstone of democratic governance, yet whether voters effectively punish corruption remains theoretically and empirically contested. While canonical models predict that corruption revelations reduce incumbent support, strategic voting considerations-especially beliefs about others' behavior-can yield ambiguous accountability outcomes. We exploit a major corruption scandal involving Japan's ruling party during a national election to examine how social information shapes electoral responses to misconduct. In a pre-registered field experiment, we randomly provided voters with information about prevailing social norms of intolerance toward the scandal. This intervention significantly increased overall turnout and challenger support, particularly among swing voters, consistent with enhanced accountability. Yet the same treatment increased incumbent support among ruling-party loyalists. We show that these heterogeneous effects are systematically driven by voters' prior beliefs about others' voting intentions: those expecting others to punish sanctioned more when learning they would not, whereas those expecting tolerance defended more when learning others would punish. These findings reconcile conflicting evidence on electoral accountability by showing how strategic considerations fundamentally shape democratic sanctioning, and suggest that information campaigns can either strengthen or undermine accountability depending on the distribution of voter expectations, with important implications for anti-corruption interventions.
Keywords: 330; Political accountability; corruption; misperception; social norm; strategic voting; moral; partisan identity; information campaign